PENGARUH PUPUK ORGANIK CAIR LIMBAH KULIT PISANG DAN BOKASHI JERAMI PADI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Lycopersicum esculentum Mill .) - Risnawati Risnawati; Rini Susanti; Mukhtar Yusuf; Ihsanul Hadi; Muhammad Alqamari (Fakultas Pertanian, Universitas Janabadra, 2023)
The tomato plant is a vegetable plant that contains lots of vitamins and minerals that are needed by humans to complete their nutritional needs in life. One effort to increase tomato production is to provide fertilizer containing macro and micro nutrients that are appropriate for plant growth. The purpose of this study was to determine the effect of liquid organic fertilizer from banana peel waste and rice straw bokashi on the growth and production of tomato plants (Lycopersicum Esculentum Mill.). The design used was a factorial randomized block design (RBD) with 2 factors studied, namely: Banana peel POC factor (K) with 4 levels, namely: K0 = control, K1 = 200 ml, and K2 = 400 ml , K3 = 600 ml . The rice straw bokashi factor (P) consists of 3 levels, namely P1 = 300 grams, P2 = 600 grams and P3 = 900 grams. Parameters observed were plant height, number of branches, flowering age, number of fruit bunches, number of fruits per plant, number of fruits per plot, fruit weight per plant, fruit weight per plot. The observed data were continued with Duncan's mean difference test (DMRT). The results showed that the POC treatment of banana peels had no significant effect on all observed parameters. In the bokashi treatment, rice straw had a significant effect on the parameters of the number of flower bunches, the number of fruit planted and the number of fruit per plot but had no significant effect on the observation of plant height, number of branches, flowering age, fruit weight per plant and fruit weight per plotINTISARITanaman tomat merupakan tanaman sayuran banyak mengandung vitamin dan mineral yang sangat dibutuhkan oleh manusia untuk melengkapi keperluan gizi dalam hidupnya. Salah satu usaha untuk meningkatkan produksi tomat adalah memberikan pupuk yang mengandung unsur hara makro dan mikro yang tepat untuk pertumbuhan tanaman. Tujuan penelitian ini untuk mengetahui pengaruh pupuk organic cair limbah kulit pisang dan bokashi jerami padi terhadap pertumbuhan dan produksi tanaman tomat (Lycopersicum Esculentum Mill .). Rancangan yang digunakan adalah Rancangan Acak Kelompok Faktorial (RAK) dengan 2 faktor yang diteliti, yaitu: Faktor POC kulit pisang (K) dengan 4 taraf yaitu : K0= kontrol, K1= 200 ml, dan K2=400 ml , K3 = 600 ml. Faktor bokashi jerami padi (P)yang terdiri dari 3 taraf yaitu P1 = 300 gram, P2 = 600gram dan P3 = 900 gram. Parameter yang diamati adalah tinggi tanaman, jumlah cabang, umur berbunga, jumlah tandan buah, jumlah buah per tanaman, jumlah buah per plot, berat buah per tanaman, berat buah per plot. Data hasil pengamatan dilanjutkan dengan uji beda rataan menurut Duncan (DMRT). Hasil penelitian menunjukkan bahwa perlakuan POC kulit pisang memberikan pengaruh tidak nyata terhadap seluruh parameter pengamatan. Pada perlakuan bokashi jerami padi memberikan pengaruh nyata terhadap parameter jumlah tandan bunga, jumlah buah pertanaman dan jumlah buah per plot tetapi berpengaruh tidak nyata terhadap pengamatan tinggi tanaman, jumlah cabang, umur berbunga, berat buah per tanaman dan berat buah per plot